The development of bronchoscopy in China: a national cross-sectional study - Shi, Dongchen; Li, Fuqi; Wang, Kaicheng; Kong, Chen; Huang, Haidong; Li, Qiang; Jin, Faguang; Hu, Chengping; Wang, Changhui; Shi, Hui; Hu, Zhenli; Dong, Yuchao; et al. (Journal of Cancer, 2020)
Objective: To investigate the development of bronchoscopy in China and compare it with its application in the early 21st century.
CRIS-Team WoS Importer:2020-08-21